HUBUNGAN PENGETAHUAN, SIKAP DAN TINDAKAN IBU DENGAN KEJADIAN PNEUMONIA PADA BALITA DI IRNA ANAK RSMH PALEMBANG TAHUN 2008 - Muchlis Riza; Sherli Shobur (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Pneumonia is a chafing lung caused by all kinds of aetiology such as bacterium, virus, fungi and foreign object.(1) Every year the pneumonia kills over 2 million children in the world. It is more of the children’s death than a malaria, a threw and a brittle syndrome of body’s impenetrability (AIDS).(2) Pneumonia represents cause of the death on number three after cardiovascular and tuberculosis in Indonesia. Patient’s pneumonia data on infant in Hospital of Dr. Mohammad Hoesin Palembang in 2007 has as much as 303 patients and in 2007 as much as 308 patients.The research purpose is to know the relationship among mother’s knowledge, attitude and action of pneumonia occurrence to an infant on a pediatric room in Hospital of Dr. Mohammad Hoesin Palembang. This research type is analytic research by using crosscut device planning (conducted in a certain deadline) or cross sectional. That is made by approach, observation and data collecting at one blow. Research population is taken on the whole mother who has infant’s pneumonia treatment. And in the other hand, sample of research is mother who has infant’s pneumonia treatment in Hospital of Dr. Mohammad Hoesin Palembang. Research result shows that there is a relationship between mother’s knowledge and pneumonia occurrence on infants based on Chi Square Test by Pvalue 0,043. There is a relationship between mother’s attitude and pneumonia occurrence on infant by Pvalue 0,02 and there is a relationship between mother’s action a pneumonia occurrence by Pvalue 0,027 on a pediatric room in Hospital of Dr. Mohammad Hoesin Palembang in 2008. The author suggests in not only a health counseling improvement of pneumonia but also given the information by a pamphlet and a poster in Hospital of Dr. Mohammad Hoesin Palembang.